Human‐Iris‐Like Aperture and Sphincter Muscle Comprising Hyperelastic Composite Hydrogels Containing Graphene Oxide. Issue 1 (12th November 2018) - Kim, Seo Gyun; Kim, Dowan; Kim, Sorie; Yoon, Jinhwan; Lee, Heon Sang
Abstract: Soft hydrogels are extensively studied for developing human‐body‐mimicking actuators because of their stimuli‐responsive volume change and elasticity. Mimicking a human eye with hydrogels is very challenging because both the large variation in the volume and the high modulus of the gels should be concurrently achieved. In the human eye, adjusting the iris for controlling the focal point and light transmittance is achieved by the contraction of the sphincter muscle. In this work, a hyperelastic poly( N ‐isopropylacrylamide) containing graphene oxide (PNIPAm/GO) composite hydrogels, which exhibits a thermo‐responsive volume phase transition is developed. The fact that the inner hole size for center‐cut hydrogels can increase or decrease during heating depending on the geometry of the hydrogels is revealed. Based on these findings, human‐iris‐like actuators capable of controlling the shape of a polydimethylsiloxane (PDMS) lens for adjusting magnification of an object is developed. When heated, the hyperelastic hydrogels act like the sphincter muscle in the eye, inducing the curvature change of the attached PDMS lens. Thus, hyperelastic hydrogels of large variation can provide an efficient platform to fabricate various soft actuation systems. Abstract : A human‐iris‐like actuator comprising hyperelastic composite hydrogels, which shows a volume change in response to the external stimuli is prepared. The fact that the focal point of the polydimethylsiloxane lens can be controlled by the volume change of hyperelastic hydrogels is demonstrated.